"A scrapbook of you + me": Intermediality and Bookish Nostalgia in J. J. Abrams and Doug Dorst's S. (April 2017) - Tanderup, Sara
Abstract : This article reads J. J. Abrams and Doug Dorst's S . (2013) as a reflection of the changing status and function of the printed novel in the digital age. As an experimental novel with yellowing pages and handwriting in the margins, S . appears to reflect a "material turn" in literature. It celebrates the book as a space of intimacy and memory, positioned in opposition to new digital media. However, the article argues that S . is also fundamentally and paradoxically grounded in digital culture. Drawing on the work of, for example, N. Katherine Hayles, Bill Brown, and Henry Jenkins, I point to a tension in S . It does at once (1) nostalgically celebrate the "aesthetics of bookishness" and (2) embrace a modern media culture where literature takes place beyond the book and between media.